ARSITEKTUR ENTERPRISE SISTEM INFORMASI PENERIMAAN SISWA BARU (STUDI KASUS : SMP KRISTEN 2 BANDAR JAYA) - Primawan Adrian Sitinja; Damayanti Damayanti; Rusliyawati Rusliyawati; M. Ghufroni An'ars (Universitas Teknokrat Indonesia, 2022)
SMP Kristen 2 Bandar Jaya is one of the private junior high schools in Central Lampung. Currently, the process of admitting new students at the SMP Kristen 2 Bandar Jaya is still carried out in a conventional way, so the committee is still having difficulties in managing the registrant files and ranking the written test results. This research is focused on developing a new student admission system at SMP Kristen 2 Bandar Jaya. The system development method used in this research is the Extreme Programming Method and the system design uses the Unified Modeling Language (UML). The implementation of this system uses Dreamweaver and MySQL as databases, as well as system testing using ISO 9126. The results achieved based on this research is a web-based new admissions information system. The system built can provide information about new student admissions for prospective students who will register at SMP Kristen 2 Bandar Jaya. This system can assist the committee in managing registrant files, conducting online tests, and also being able to display the ranking of test results